Investigating Correlation Between Spiritual Health and Public Health Among Mothers of Mentally Disabled Children - Afsar Omidi; Nahid Mohammadi; Seyyedeh Zinat Nazari; Leili Tapak (Hamadan University of Medical Sciences, 2019)
Introduction: A mentally retarded child puts burden and responsibility on their family, especially the mother, and disturbs her general health. Since spiritual wellbeing is one of the most important sociocultural factors related to health, this study aimed to determine the correlation between spiritual health and public health among mothers of mentally disabled children in Hamadan. Methods: This descriptive cross-sectional study was a correlation study on 165 mothers with mentally disabled children who were studying at special schools in Hamadan in spring of 2017 who were selected using available sampling method. Data were collected by General Health Questionnaire (GHQ-28), Spiritual Well Being (SWB), and demographic Questionnaire that were completed by mothers on the presence of a researcher. SPSS 23 software was used to analyze the data and descriptive and correlation tests were used. Results: The results of this study showed that the mean age of mothers was 37.3 ± 6.3. The gender of mentally disabled children was 52.7% male and 47.3% female. 10% of mothers reported health disorders, as well as the spiritual level of the majority of mothers was moderate (63%). There was a significant relationship between spiritual health and public health (P <0/05). Conclusion: The results of this study showed that there is a revers relationship between spiritual health and health disorders, so that the promotion of spiritual health will promote public health and reduce health disorders, including anxiety among mothers. Given the important role of mothers in the care for their children, the design of educational programs aimed at improving the health of mothers should be a priority.